Single-cell gel (comet) assay detects primary DNA damage in nonneoplastic urothelial cells of smokers and ex-smokers - Gontijo, AMDC; Elias, F. N.; Salvadori, Daisy Maria Favero [UNESP]; de Oliveira, MLCS; Corrêa, Luiz Antonio [UNESP]; Goldberg, José [UNESP]; Trindade, JCD; de Camargo, JLV (American Association for Cancer Research (AACR), 2001)
A protocol for DNA damage assessment by the single-cell gel (SCG)/comet assay in human urinary bladder washing cells was established. Modifications of the standard alkaline protocol included an increase to 2% of sodium sarcosinate in the lysis solution, a reduction in the glass-slide area for comet analysis, and a cutoff value for comet head diameter of at least 30 mum, to exclude contaminating leukocytes. Distinguishing cell populations is crucial, because significant differential migration was demonstrated for transitional and nontransitional cells, phenomena that may confound the results. When applying the modified protocol to urinary bladder cells from smokers without urinary bladder neoplasia, it was possible to detect a significant (P = 0.03) increase in DNA damage as depicted by the tail moment (6.39 +/- 3.23; mean 95% confidence interval; n = 18) when compared with nonsmokers (1.94 +/- 1.41; n = 12). No significant differences were observed between ex-smokers and current smokers regarding comet parameters. Inflammation was not a confounding factor, but DNA migration increased significantly with age in nonsmokers (r = 0.68; P = 0.014). Thus, age matching should be a concern when transitional cells are analyzed in the SCG assay. As it is well known, DNA damage may trigger genomic instability, a crucial step in carcinogenesis. Therefore, the present data directly support the classification of individuals with smoking history as patients at high risk for urinary bladder cancer.